2017
DOI: 10.14746/ssllt.2017.7.3.4
|View full text |Cite
|
Sign up to set email alerts
|

The development of English grammar and reading comprehension by majority and minority language children in a bilingual primary school

Abstract: Both for the first language (L1) and for all additional languages (L2 or L3), grammatical knowledge plays a vital role in understanding texts (e.g., Grabe, 2005). However, little is known about the development and interaction of grammar and reading comprehension in beginning foreign language learning, especially with respect to children with a minority language background. This longitudinal study, therefore, examined minority and majority language children’s English grammar and reading comprehension skills. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Yet, at this point in time, there is no empirical evidence to prove this assumption right. Instead, studies in immersive English classrooms have shown that simultaneous literacy development in English and German is possible without (long-term) drawbacks in L1 literacy and L1 development (Steinlen, 2021;Wirbatz & Reckermann, 2020;Zaunbauer, 2007).…”
Section: A Glimpse Into the History Of Early Biliteracymentioning
confidence: 99%
See 3 more Smart Citations
“…Yet, at this point in time, there is no empirical evidence to prove this assumption right. Instead, studies in immersive English classrooms have shown that simultaneous literacy development in English and German is possible without (long-term) drawbacks in L1 literacy and L1 development (Steinlen, 2021;Wirbatz & Reckermann, 2020;Zaunbauer, 2007).…”
Section: A Glimpse Into the History Of Early Biliteracymentioning
confidence: 99%
“…The general aim of such bilingual programmes is to foster both FL learning and content learning (including a high level of intercultural competence), without negatively affecting pupils' first language (L1) skills or their subject knowledge (e.g. Coyle et al, 2010;Frisch, 2021;Steinlen, 2021).…”
Section: Bilingual Primary School Programmes In Germanymentioning
confidence: 99%
See 2 more Smart Citations
“…When reading English texts, the readers with enough grammar knowledge will be easy to understand the meanings of the sentences in their texts. Steinlen (2017) argues that the success of the readers to comprehend the texts depends on their grammar knowledge. They will be able to guess the meaning of the words that they do not know in their texts when they have sufficient knowledge of grammar.…”
Section: Roles Of Grammar Competence In Language Learningmentioning
confidence: 99%